THE PERFORMATIVITY OF THE YOGYAKARTA LOGO AS A CITY BRANDING - Sudarmanto, Joni Agung (Jurusan Seni dan Desain, Fakultas Sastra, Universitas Negeri Malang, 2022)
This study aims to dissect the material contained in the Yogyakarta logo and how its performance as a city branding. Furthermore, the study was carried out to see how the negotiations took place in the performativity of elements and symbols in the reflection of the people of Yogyakarta. This research uses a qualitative case study approach to examine how the community responds to the Yogyakarta logo as city branding. The responses obtained were then dissected with a performative point of view from Richard Schechner and the agency of Alfred Gell, which in this study emphasizes the logo as an agency and representation of Yogyakarta in carrying out city branding. A textual study was conducted on the Yogyakarta logo, and a contextual study was conducted on the public's response to the Yogyakarta logo. The formal object of this research is the performativity of the Yogyakarta logo as city branding. The results showed that every visual element in the logo of Yogyakarta represents the life of the people in Yogyakarta. The emphasis is also placed on a modern perspective in typography and a trend towards a modern logo. Furthermore, the performativity of the elements that negotiate with the community's response is influenced by the public perception built in Yogyakarta. Therefore, the performativity aspect lies in the triadic relationship between visual (text), contextual elements related to daily life, and history so that the agency process by the Yogyakarta City logo runs optimally.